Strategi Pengembangan SDM dalam Meningkatkan kompetensi Staf pada Klinik Hewan Myttens Petcare - Desi Nurhalimah; Denny Murdani (Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to analyze the human resource development (HRD) strategies implemented at Myttens Petcare Veterinary Clinic and evaluate their impact on staff competency improvement. This research employs a qualitative method using a case study approach. Data were collected through in-depth interviews, direct observation, and documentation. Informants included the clinic owner and staff from the receptionist, paramedic, and groomer divisions. The findings show that the HRD strategies included internal and external training, periodic evaluations, daily briefings, and peer discussions. These strategies positively influenced staff competence, self-confidence, and collaboration. Performance evaluations showed an average score of 4.36, indicating a “good” category. These findings support the HRD theories by Hasibuan, Mathis & Jackson, and Handoko. The study recommends a participatory, adaptive HRD model grounded in a family-oriented work culture, which may be adopted by other veterinary clinics to improve service quality..